STATISTICAL STUDY OF CHANGE IN HUMAN LIFESTYLE AFTER COVID-19: A CASE STUDY - Patil, Pitambar Y. (International Journal of Research -GRANTHAALAYAH, 2024)
This research article studies the change in human lifestyle after Covid–19 pandemic. We have conducted an online sample survey about various factors associated with human life after the COVID-19 pandemic. After this survey, we have classified responses into various categories, especially infected and non-infected by COVID–19. We test whether various human lifestyles in all respondents are divided into the ratio 1:1 or more proportion belonging to the specified human lifestyle. We also compare the proportions of various human lifestyles in infected and non-infected categories. We compute the Z-statistic to test the statistical significance of these proportions of human behaviors. p–values are obtained for each of these tests, which helps us to know how much the observed value of Z-Statistic is significant for rejecting the null hypotheses about various human lifestyles. p–values are probabilities, which always take values between 0 to 1. The smaller p-value supports rejecting the null hypothesis in favor of its alternative, whereas the larger p–value supports accepting the null hypothesis.